Terengganu land of golden opportunities (Kuala Terengganu : Terengganu State Economic Planning Unit, 2000)
Program on the planning on economic growth in Terengganu. Explore all opportunities and place to be developed
VCD format
Keywords: Terengganu -- Economic conditions; Terengganu -- Industries